Law of Necessity: Introduction and Comparative Study of Islamic and Western Thoughts - Mujeeb ur Rehman (Journal of Islamic and Religious Studies, 2018)
Mankind among the other creatures is a superior creation of Allah. Though he has been gifted and empowered with strength and logic, yet at times he becomes vulnerable or unfortified during his life span. To handle and manage such weak events and moments of life, Allah has laid down a law of necessity upon him. Since Islam is the religion of ease, comfort and compassion in all matters, therefore on the one hand it provides the regular course of system for the usual and routine matters, while on the other hand it promulgates the law of necessity for unusual and extra ordinary matters. The Western legal system also recognizes such concept of law, but as compared to Islamic concept of law of necessity it does not cover all the aspects of human vulnerability. This paper puts forth a discourse that how this exceptional segment of law can be applied and what is the difference between the Islamic concept of law of necessity and that of which the western legal system has.